Inhibition of PirB Activity by TAT-PEP Improves Mouse Motor Ability and Cognitive Behavior - Mi, Ya-Jing; Chen, Hai; Guo, Na; Sun, Meng-Yi; Zhao, Zhao-Hua; Gao, Xing-Chun; Wang, Xiao-Long; Zhang, Rui-San; Zhou, Jiang-Bing; Gou, Xing-Chun (Frontiers in Aging Neuroscience, 2017)
Paired immunoglobulin-like receptor B (PirB), a functional receptor for myelin-associated inhibitory proteins, plays an important role in axon regeneration in injured brains. However, its role in normal brain function with age has not been previously investigated. Therefore in this study, we examined the expression level of PirB in the cerebral cortex, hippocampus and cerebellum of mice at 1 month, 3 months, and 18 months of age. The results showed that the expression of PirB increased with age. We further demonstrated that overexpression of PirB inhibited neurite outgrowth in PC12 cells, and this inhibitory activity of PirB could be reversed by TAT-PEP, which is a recombinant soluble PirB ectodomain fused with TAT domain for blood-brain barrier penetration. In vivo study, intraperitoneal administration of TAT-PEP was capable of enhancing motor capacity and spatial learning and memory in mice, which appeared to be mediated through regulation of brain-derived neurotrophic factor secretion. Our study suggests that PirB is associated with aging and TAT-PEP may be a promising therapeutic agent for modulation of age-related motor and cognitive dysfunctions.